Comprehensive and comparative exploration of the Atp7b−/− mouse plasma proteome. Issue 2 (9th December 2019) - Lacombe, Maud; Jaquinod, Michel; Belmudes, Lucid; Couté, Yohann; Ramus, Claire; Combes, Florence; Burger, Thomas; Mintz, Elisabeth; Barthelon, Justine; Leroy, Vincent; Poujois, Aurélia; Lachaux, Alain; et al.
Abstract : Wilson's disease (WD) is a rare genetic disease caused by mutations in the ATP7B gene. In this study, we used MS-based proteomics to explore the plasma proteome of the Atp7b −/− mouse, a genetic and phenotypic model for WD. Abstract : Wilson's disease (WD), a rare genetic disease caused by mutations in the ATP7B gene, is associated with altered expression and/or function of the copper-transporting ATP7B protein, leading to massive toxic accumulation of copper in the liver and brain. The Atp7b −/− mouse, a genetic and phenotypic model of WD, was developed to provide new insights into the pathogenic mechanisms of WD. Many plasma proteins are secreted by the liver, and impairment of liver function can trigger changes to the plasma proteome. High standard proteomics workflows can identify such changes. Here, we explored the plasma proteome of the Atp7b −/− mouse using a mass spectrometry (MS)-based proteomics workflow combining unbiased discovery analysis followed by targeted quantification. Among the 367 unique plasma proteins identified, 7 proteins were confirmed as differentially abundant between Atp7b −/− mice and wild-type littermates, and were directly linked to WD pathophysiology (regeneration of liver parenchyma, plasma iron depletion, etc. ). We then adapted our targeted proteomics assay to quantify human orthologues of these proteins in plasma from copper-chelator-treated WD patients. The plasma proteome changes observed in the Atp7b −/− mouse were not confirmed in these samples, except for alpha-1 antichymotrypsin, levels of which were decreased in WD patients compared to healthy individuals. Plasma ceruloplasmin was investigated in both the Atp7b −/− mouse model and human patients; it was significantly decreased in the human form of WD only. In conclusion, MS-based proteomics is a method of choice to identify proteome changes in murine models of disrupted metal homeostasis, and allows their validation in human cohorts.